THE APPLICATION OF DEMONSTRATIVE AND POSSESSIVE PRONOUNS IN ENGLISH. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the use of demonstrative and possessive pronouns in the English language, which play a critical role in communication and expression. Demonstrative pronouns (this, that, these, those) and possessive pronouns (my, your, his, her, its, our, their) are essential for conveying relationships and indicating specificity in discourse. The article analyzes the differences between these pronouns, their grammatical characteristics, and their contextual applications. Through examples, the article demonstrates how demonstrative and possessive pronouns can be effectively used in various situations. It aims to provide guidance for English language learners in mastering the correct and efficient use of these pronouns.